Report of Eleven Patients of Subcutaneous Panniculitis-Like T-Cell Lymphoma: Clinicopathologic Features, 18F-FDG PET/CT Findings and Outcome - Jiang, Maoqing; Zhao, Long; Zheng, Jianjun; Zhang, Jingfeng; Chen, Ping; Zhou, Wenlan (Frontiers in Oncology, 2021)
Objectives: Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a fairly rare subtype of primary cutaneous lymphoma. This study aims to investigate the clinicopathologic features, 18F-FDG PET/CT findings and outcome of patients with SPTCL. Methods: A retrospective single-center study of 11 patients with SPTCL were enrolled between August 2010 and March 2020. A total of 26 18F-FDG PET/CT scans were performed and the initial and follow-up PET/CT imaging features, clinicopathologic and immunohistochemical characteristics, and outcome were analyzed. Results: The male-to-female ratio was 1.2. The mean age at diagnosis was 24.2 years (age range: 13-48 years). Histopathological examinations revealed atypical T-lymphocytes rimming of individual subcutaneous adipocytes, mostly with CD2+, CD3+, CD4-, CD5+, CD8+, CD56-, T-cell intracellular antigen-1+, Granzyme B+ and high Ki-67 index. Multiple large skin ulcerations with a maximum diameter of 10 cm were observed in one of the 11 patients (9.1%, 1/11) and hemophagocytic syndrome was found in another one. At initial PET/CT scans, the lesions in all 11 patients showed increased uptake of 18F-FDG with a wide range of maximum standard uptake value (SUVmax) from 2.0 to 14.9. The morphology of the lesions presented as multiple nodules and/or disseminated plaques mainly involving the trunk and/or limbs. Five patients had extracutaneous non-lymph node lesions with SUVmax of 5.6 ± 2.8 on 18F-FDG PET/CT. No significant correlation between SUVmax and Ki-67 index was observed (r=0.19, P>0.05). Following-up 18F-FDG PET/CT scans in 6 patients showed complete remission of the disease in 2, partial remission in 3 and progressive disease in one. During the follow-up period, there was no death except for the patient with multiple ulcerations who died 4 months after diagnosis of SPTCL. Conclusions: SPTCL may be a group of heterogeneous diseases with varying degrees of 18F-FDG uptake. 18F-FDG PET/CT demonstrates to be useful in detecting disease extent, providing diagnostic work-up, staging and evaluating treatment response of SPTCL. Multiple large skin ulcerations may be a factor of poor prognosis for patients with SPTCL.